Komposisi dan Keanekaragaman Tumbuhan Bawah pada Tegakan Akasia di Taman Nasional Baluran Jawa Timur - Djufri Djufri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
The research was done in Baluran National Park, Banyuwangi East Java in April to June 2004. The objectives of this research are to determine species composition, importance value of species, diversity index and evenness index, similarity index, distribution pattern of species, and species association. This research used quadratic method. The determination of the species distribution was calculated using Poisson distribution formula. The determination of association was calculated using contingency table and classification of community using similarity index formula and cluster analysis. The results of this research indicated that, there were 63 species of plants including 18 family. The importance value was between 0, 97-42,58 and species with high and medium importance value are Brachiaria reptans, Tespesisa lanpas, Oplismenus burmanii, Dichantium coricosum, Axonopus compressus, and Synedrella nudiflora. The diversity index was between 1, 1504-2, 7556 and evenness index was between 1, 1067-1, 7854. The distribution pattern of species indicated that 16 species were distributed in a clumped, 5 species were in a reguler, and 4 species were at random distribution pattern. The grass-group tend to have a clumped distribution pattern, and non-grass-group tend to have a reguler or random distribution pattern. The determine association indicated that 6 species had very high association index :: Brachiaria reptans, Dichantium coricosum, Tespesia lanpas, Achyrantes aspera, Stachytarpeta indica, Axonopus compressus and Oplismenus burmanii. The result of classification community indicated that savanna Baluran National Park can be devided three group (a). Open savanna no A. nilotica stand, (b). Savanna with density of A. nilotica stand 1500-3000 individuals/ha, and (c). savanna with dense  A. nilotica stand  3000 individuals/ha.